Impacto de um programa de exercícios físicos na funcionalidade de mulheres idosas - Hausen, Lia (2023)
The aging process is a growing reality worldwide, especially for women, making it essential to direct our gaze to the various faces that this process denotes. One angle that needs to be explored is the limitations that arise with age, including episodes of falls, which are often due to balance deficits and gait limitations. The decline in strength and flexibility in the feet and ankles, as well as the limitations in activities of daily living (ADLs), demonstrates a gradual loss of handgrip strength (HGS) and hand and foot mobility, which consequently leads to a loss of autonomy and functionality since the hands and feet help us with the basic tasks of daily living (DL). This study aimed to evaluate the effectiveness of a physical exercise (PE) protocol in improving balance, posture, and proprioception in elderly women, as well as their functionality. A longitudinal intervention study was developed with a group of 18 women, with a mean age of 70 years (SD = 7.2), from the municipality of Erechim-RS (Brazil), who participated in 24 sessions of PE interventions for feet, ankles, hands, and forearms. The International Physical Activity Questionnaire (IPAQ) and the Falls Effectiveness Scale - International in Brazilian Elderly (FES-I-BRAZIL) were applied. Afterward, the first evaluations (pre-interventions) were carried out with the aid of the baropodometer (BaroScan®), where the plantar pressure was verified to describe its changes, the type of step, the postural balance, and quantify the center of pressure (CoP). Likewise, the dynamometer (Crown®) manual model 100 Kgf was used to verify the Handgrip Strength (FPM). The same evaluations were performed pre and post-interventions. This study is described in our first production (Chapter 3). For the the theoretical foundation, a systematic review was elaborated (2rd production/Chapter 4), which confirmed the research problem that led us to carry out this study, our 3rd production (Chapter 5) validates our findings by addressing the understanding of the impact that the proposed interventions had on the lives of elderly women individuals. This process led us to conclude that the extremities need attention since interventions that include PE aimed at increasing the strength and flexibility of the feet and ankles significantly improve posture and proprioception and consequently reduce falls. As well as PE which includes interventions to improve the strength and flexibility of the hands and forearms, HGS, mobility, and functionality of older women. Therefore, older women benefit from increased autonomy and quality of life (QoL)